Electrolyte and lithium ion battery

By using additives with -Si-O-Si-groups to form a protective layer in the electrolyte of the lithium-ion battery, the problem of volume expansion of the silicon-based negative electrode material is solved, and the safety and circulation performance of the lithium-ion battery are improved.

CN119324253AActive Publication Date: 2025-01-17ENVISION DYNAMICS TECH (JIANGSU) CO LTD +4

Patent Information

Application Number
CN202310879228.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material in lithium-ion batteries leads to powder removal during charging and discharging, affecting the safety and circulation performance of the battery.

Method used

The first additive with a -Si-O-Si-group structure is added to the electrolyte, and a Si-O-Si bond is formed by reacting with the silicon hydroxyl group on the surface of the silicon-based negative electrode material to form a protective layer to reduce the volume expansion. The negative effect is made and the acidic substance in the electrolyte is absorbed by the second additive to protect the first additive.

Benefits of technology

It effectively suppresses the volume expansion of silicon-based negative electrode material, improves the safety performance, storage performance and circulation performance of lithium-ion batteries, and improves the battery's circulation capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344777510000021
    Figure BDA0004344777510000021
  • Figure BDA0004344777510000041
    Figure BDA0004344777510000041
  • Figure BDA0004344777510000111
    Figure BDA0004344777510000111
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium ion battery, and belongs to the technical field of secondary batteries, and the electrolyte comprises a lithium salt, an organic solvent and a first additive. The first additive with a-Si-O-Si-group structure is added into the electrolyte, and the-Si-O-Si-group in the first additive reacts with residual silicon hydroxyl on the surface of the silicon-based negative electrode material to form a Si-O-Si bond, so that the first additive is attached and fixed on the surface of the silicon-based negative electrode material; when the volume of the silicon-based negative electrode material is expanded, groups with relatively large steric hindrance on the periphery of a Si-O-Si bond are diffused on the surface of the silicon-based negative electrode material, so that a fresh exposed surface caused by the volume expansion of the silicon-based negative electrode material is reduced, and the negative influence of the volume expansion of the silicon-based negative electrode material on the lithium ion battery is inhibited; further, the safety performance, the storage performance and the cycle performance of the lithium ion battery assembled with the silicon-based negative electrode are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to an electrolyte and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles due to their high energy density and long cycle life. With the development of the electric vehicle industry, the driving range has become an important reason restricting the further development of lithium-ion batteries.

[0003] Silicon-based negative electrode materials have extremely high theoretical specific capacity (4200mAh / g), which can greatly improve the energy density of negative electrode sheets and are widely considered to be the preferred choice for negative electrodes in next-generation products.

[0004] However, although silicon-based negative electrode materials have ideal specific capacity, the volume expansion effect of silicon-based negative electrode materials themselves during the lithium insertion and delithiation process of charging and discharging can easily lead to the pulverization and detachment of silicon-based negative electrode materials on the negative electrode sheet, causing rapid decay of battery capacity, making the safety and cycle performance of lithium-ion batteries equipped with silicon-based negative electrodes poor in practical applications.

[0005] Therefore, it is necessary to design an electrolyte and a lithium-ion battery that can suppress the negative impact of the expansion of silicon-based negative electrode materials in lithium-ion batteries, thereby solving the above problems. Summary of the invention

[0006] In view of the above shortcomings of the prior art, the present invention provides an electrolyte and a lithium-ion battery for inhibiting the volume expansion of silicon-based negative electrode materials in lithium-ion batteries during the charging and discharging process, thereby reducing the negative impact of the volume expansion of silicon-based negative electrode materials on lithium-ion batteries.

[0007] To achieve the above object and other related objects, the present invention provides an electrolyte, which includes: a lithium salt, an organic solvent and a first additive.

[0008] The first additive includes one or more compounds represented by structural formula (1):

[0009]

[0010] Wherein, R1, R2, R3, R4 and R5 are each independently selected from methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl.

[0011] In one example of the present invention, the compound represented by the structural formula (1) contains an unsaturated bond.

[0012] In an example of the present invention, the mass percentage of the first additive in the electrolyte is 0.1% to 1%.

[0013] In one example of the present invention, the electrolyte further includes a second additive, and the second additive includes one or more compounds represented by structural formula (2):

[0014] R6-N=C=N-R7 (2)

[0016] Wherein, R6 and R7 are each independently selected from an alkane group or a cycloalkane group.

[0017] In an example of the present invention, the mass percentage of the second additive in the electrolyte is 0.1% to 0.6%.

[0018] In an example of the present invention, the organic solvent includes cyclic carbonate and linear carbonate.

[0019] In one example of the present invention, the cyclic carbonate includes one or both of ethylene carbonate (EC) and propylene carbonate (PC); the linear carbonate includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC).

[0020] In an example of the present invention, the mass percentage of the cyclic carbonate in the organic solvent is 10% to 40%; the mass percentage of the linear carbonate in the organic solvent is 10% to 80%.

[0021] The present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte described in any one of the above examples.

[0022] The present invention adds a first additive having a -Si-O-Si- group structure to the electrolyte, and uses the -Si-O-Si- group in the first additive to react with the residual silanol group on the surface of the silicon-based negative electrode material, so that the first additive forms a Si-O-Si bond on the surface of the silicon-based negative electrode material, thereby adhering to the surface of the silicon-based negative electrode material. When the volume of the silicon-based negative electrode material expands, the groups with large steric hindrance on the periphery of the Si-O-Si bond in the first additive will diffuse on the surface of the silicon-based negative electrode material as the volume of the silicon-based negative electrode material expands, thereby reducing the fresh exposed surface caused by the volume expansion of the silicon-based negative electrode material, and inhibiting the negative impact of the volume expansion of the silicon-based negative electrode material on the lithium-ion battery, thereby improving the safety performance, storage performance and cycle performance of the lithium-ion battery equipped with the silicon-based negative electrode. DETAILED DESCRIPTION

[0023] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0024] It should be noted that, in the absence of conflict, the features in the following examples and embodiments can be combined with each other. It should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0025] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.

[0026] The present invention provides an electrolyte and a lithium ion battery. A first additive having a -Si-O-Si- group structure is introduced into the electrolyte. The -Si-O-Si- group in the first additive reacts with residual silanol groups on the surface of a silicon-based negative electrode material to form a Si-O-Si bond, so that the first additive forms a protective layer with a large steric hindrance on the surface of the silicon-based negative electrode material, thereby eliminating the stress generated on the surface of the material when the silicon-based negative electrode material expands in volume, reducing the newly exposed area on the surface of the silicon-based negative electrode material, thereby suppressing the negative impact of the volume expansion of the silicon-based negative electrode material on the lithium ion battery, and improving the safety performance, storage performance and cycle performance of the lithium ion battery.

[0027] The electrolyte provided by the present invention comprises a lithium salt, an organic solvent and a first additive. The structure of the first additive is shown in structural formula (1):

[0028]

[0029] In the structural formula (1), R1, R2, R3, R4 and R5 are each independently selected from any one of a methyl group, a tert-butyl group, a 1,1-dimethoxyethyl ether group and a 1,1-diethylpropyl group. That is, R1 can be methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl, R2 can be methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl, R3 can be methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl, R4 can be methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl, and R5 can be methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl; wherein R1, R2, R3, R4 and R5 can all be the same, for example, R1, R2, R3, R4 and R5 are all methyl or tert-butyl; R1, R2, R3, R4 and R5 can also be partially the same, for example, R1, R2, R3 are methyl, R4, R5 are 1,1-dimethoxyethyl ether, and so on. The first additive may be one of the compounds represented by the structural formula (1), or a combination of two or more of them mixed in any proportion.

[0030] In lithium-ion batteries equipped with silicon-based negative electrodes, the first additive added to the electrolyte can use its own -Si-O-Si- group to react with the residual silanol groups on the surface of the silicon-based negative electrode material. The -Si-O-Si- group of the first additive forms a Si-O-Si bond on the surface of the silicon-based negative electrode material, thereby allowing the first additive to be attached and fixed to the surface of the silicon-based negative electrode material through the Si-O-Si bond. The attached first additive uses the R1, R2, R3, R4 and R5 groups outside the Si-O-Si bond to coat and protect the surface of the silicon-based negative electrode material.

[0031] When the silicon-based negative electrode material expands in volume during the charge and discharge process of the battery, the attached first additive utilizes the R1, R2, R3, R4 and R5 groups with large spatial hindrance around the Si-O-Si bond to diffuse on the surface of the silicon-based negative electrode material, thereby eliminating the surface stress of the silicon-based negative electrode material during expansion, reducing the fresh exposed surface caused by the volume expansion of the silicon-based negative electrode material, avoiding cracks and pulverization on the surface of the silicon-based negative electrode material, and thus inhibiting the negative impact of the volume expansion of the silicon-based negative electrode material on the capacity and cycle performance of the lithium-ion battery.

[0032] In some embodiments, the chemical structure of the first additive also includes an unsaturated bond, which can cause the first additive compound adjacent to the surface of the silicon-based negative electrode material to polymerize, thereby enhancing the adhesion strength of the first additive on the surface of the silicon-based negative electrode material and reducing the failure of the first additive caused by the breaking of Si-O-Si bonds when the silicon-based negative electrode material expands.

[0033] In some embodiments, the mass percentage of the first additive in the non-aqueous electrolyte is 0.1% to 1%, for example, 0.1%, 0.3%, 0.5%, 0.8% or 1%, etc.

[0034] In some preferred embodiments, the mass percentage of the first additive in the non-aqueous electrolyte is 0.5% to 1%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc. When the mass percentage of the first additive in the electrolyte is within the above range, the cycle performance improvement effect of the lithium-ion battery equipped with the silicon-based negative electrode is the best.

[0035] In some implementations, the electrolyte further includes a second additive, and the structure of the second additive is shown in structural formula (2):

[0036] R6-N=C=N-R7 (2)

[0038] In the structural formula (2), R6 and R7 are each independently selected from an alkane group or a cycloalkane group. That is, R6 can be an alkane group or a cycloalkane group, and R7 can be an alkane group or a cycloalkane group, wherein R6 and R7 can be the same, for example, R6 and R7 are both ethyl, or both cyclohexyl, etc.; R6 and R7 can also be different, for example, R6 is n-butyl, R7 is cyclohexyl, etc. The second additive can be one of the compounds shown in the structural formula (2), or a combination of two or more compounds mixed in any proportion.

[0039] In lithium-ion batteries equipped with silicon-based negative electrodes, the Si-O-Si bonds formed by the first additive attached to the surface of the silicon-based negative electrode material are easily acidified by the acidic substances (such as HF) in the electrolyte, resulting in the breaking of the Si-O bonds, which reduces the inhibitory effect of the first additive on the volume expansion of the silicon-based negative electrode material. To solve the above problem, the first additive and the second additive are added in combination in the electrolyte. The second additive can absorb water and acidic substances in the electrolyte to reduce the effect of acidic substances (such as HF) formed in the electrolyte on the first additive, thereby helping to enhance the inhibitory effect of the first additive on the volume expansion of the silicon-based negative electrode material, as well as the improvement effect on the capacity and cycle performance of the lithium-ion battery.

[0040] In some embodiments, the mass percentage of the second additive in the non-aqueous electrolyte is 0.1% to 0.6%, for example, 0.1%, 0.3% or 0.6%, etc. When the mass percentage of the second additive in the electrolyte is within the above range, the first additive attached to the surface of the silicon-based negative electrode material is best protected, and the cycle performance of the lithium-ion battery equipped with the silicon-based negative electrode is best improved.

[0041] The organic solvent in the electrolyte can be selected from conventional solvent combinations in the art. In the present invention, the organic solvent includes cyclic carbonates and linear carbonates, wherein the mass of the cyclic carbonate accounts for 10% to 40% of the total mass of the organic solvent, for example, 10%, 20% or 40%, and the mass of the linear carbonate accounts for 10% to 80% of the total mass of the organic solvent, for example, 10%, 30%, 50% or 80%, etc.

[0042] As an example, the cyclic carbonate includes one or both of ethylene carbonate (EC) and propylene carbonate (PC). For example, the cyclic carbonate can be ethylene carbonate, propylene carbonate, or a mixture of ethylene carbonate and propylene carbonate in any proportion.

[0043] Linear carbonates include one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), that is, the linear carbonates can be any one of the above-listed types, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate; the linear carbonates can also be a combination of any two or three of the above-listed types, such as a combination of dimethyl carbonate and diethyl carbonate, or a combination of diethyl carbonate and ethyl methyl carbonate, or a combination of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. It should be noted that when the linear carbonate is a composition, there is no restriction on the ratio between the components in the composition, and any ratio can be mixed.

[0044] The lithium salt in the electrolyte can be selected from conventional lithium salt types in the art. As an example, the lithium salt includes lithium bis(fluorosulfonyl)imide (LiFSI) and / or lithium hexafluorophosphate (LiPF6). That is, the lithium salt can be lithium bis(fluorosulfonyl)imide (LiFSI) alone, lithium hexafluorophosphate (LiPF6) alone, or a combination of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) mixed in any proportion.

[0045] In some embodiments, the mass percentage of the lithium salt in the electrolyte is 8% to 20%. Further, the mass percentage of the lithium salt in the electrolyte is 10% to 17%, such as 10%, 13%, 15% or 17%, etc.

[0046] The electrolyte of the present invention can be prepared according to conventional preparation methods, for example, the organic solvents are mixed and stirred, and then the lithium salt is added to the mixed solvent under stirring conditions, and the stirring is continued until the lithium salt is completely dissolved, and finally the first additive and the second additive are added and stirred evenly to obtain the electrolyte.

[0047] The present invention also provides a lithium-ion battery, a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and the electrolyte described above in the present invention. During the battery charging and discharging process, lithium ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet to play a role of isolation; the electrolyte plays a role of conducting lithium ions between the positive electrode sheet and the negative electrode sheet.

[0048] Among them, the electrolyte is the electrolyte described above in the present invention. Since the first additive in the electrolyte is attached and fixed on the surface of the silicon-based negative electrode material through the reaction of the -Si-O-Si- group and the silanol group, and the surface of the silicon-based negative electrode material is coated and protected by the group with a large steric hindrance around the Si-O-Si bond, the newly exposed surface area when the silicon-based negative electrode material expands in volume is reduced, and the negative impact of the volume expansion of the silicon-based negative electrode material on the lithium-ion battery is suppressed, thereby improving the safety performance, storage performance and cycle performance of the lithium-ion battery.

[0049] The composition and preparation method of lithium-ion batteries are described in detail below:

[0050] The positive electrode plate of the lithium-ion battery includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. Among them, the positive electrode current collector can be made of a material with good electrical conductivity and mechanical strength, such as aluminum foil. The positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector. The positive electrode active material layer includes a positive electrode material, a positive electrode conductive agent and a positive electrode binder. The specific types of the positive electrode material, the positive electrode conductive agent and the positive electrode binder are not specifically limited here. Materials known in the art that can be used in lithium-ion batteries can be used, and those skilled in the art can choose according to actual needs.

[0051] The positive electrode material can be selected from lithium cobalt oxide, ternary materials and lithium phosphates. Specifically, the ternary materials include but are not limited to lithium nickel cobalt manganese oxide LiNi x Co y Mn z O2 (x+y+z=1); lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The binder is selected from polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), etc. The conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them mixed in any proportion.

[0052] The positive electrode sheet can be prepared according to methods known in the art. For example, the positive electrode material, the positive electrode conductive agent and the positive electrode binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry: the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained. The ratio between the components in the positive electrode slurry can be set according to the conventional ratio, and is not limited here.

[0053] The negative electrode plate of a lithium-ion battery includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector can be made of a material with good electrical conductivity and mechanical strength, such as copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode material, a negative electrode conductive agent, a negative electrode binder and a thickener. The specific types of the negative electrode material, the negative electrode conductive agent and the negative electrode binder are not specifically limited here. Materials known in the art that can be used in lithium-ion batteries can be used, and those skilled in the art can make selections according to actual needs.

[0054] The negative electrode material is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compounds, and silicon carbon compounds, preferably silicon oxide compounds. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), or a combination of several mixed in any proportion; the thickener is selected from carboxymethyl cellulose, which can be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).

[0055] The negative electrode sheet can be prepared according to methods known in the art. For example, the negative electrode material, negative electrode binder, thickener and negative electrode conductive agent are dispersed in deionized water to form a uniform negative electrode slurry: the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet is obtained. Among them, the ratio between the components in the negative electrode slurry can be set according to the conventional ratio, and is not limited here.

[0056] The diaphragm is selected from conventional types in the art, for example, a PE porous membrane is selected as the diaphragm, the thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0057] The battery assembly is carried out according to conventional methods, for example, after preparation, the negative electrode sheet, the separator, and the positive electrode sheet are stacked in order, and placed in an aluminum plastic film to obtain a dry cell, and the dry cell is baked at 80°C to remove water. The prepared electrolyte is injected into the dry cell and packaged to obtain a finished lithium-ion battery.

[0058] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0059] The material components of Examples 1 to 7 and Comparative Example 1 refer to Table 1.

[0060] Example 1

[0061] The present embodiment provides an electrolyte, the electrolyte comprising 2% by weight of lithium hexafluorophosphate (LiPF6), 13% by weight of lithium bis(fluorosulfonyl)imide (LiFSI), and 0.1% by weight of a first additive, the first additive being a compound represented by structural formula (1), wherein R1, R2, R3, R4, and R5 groups in the first additive are methyl groups; the remainder of the electrolyte is an organic solvent, wherein the organic solvent comprises 30% of ethylene carbonate (EC), 50% of ethyl methyl carbonate (EMC), and 20% of diethyl carbonate (DEC).

[0062] The electrolyte preparation method comprises: mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20 to obtain an organic solvent; adding 2wt% of lithium hexafluorophosphate and 13wt% of lithium bis(fluorosulfonyl)imide into the organic solvent and mixing them evenly; and then adding 0.1wt% of a compound of structural formula (1) as a first additive, and mixing them evenly to obtain an electrolyte.

[0063] Example 2

[0064] In this embodiment, an electrolyte of the same system as that in Embodiment 1 is prepared. The difference between this embodiment and Embodiment 1 is that in the prepared electrolyte, the amount of the first additive is 0.5% of the mass percentage of the electrolyte.

[0065] Example 3

[0066] In this embodiment, an electrolyte of the same system as that in Embodiment 1 is prepared. The difference between this embodiment and Embodiment 1 is that in the prepared electrolyte, the amount of the first additive is 1% by mass of the electrolyte.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first additive is replaced by a second additive, the second additive is a compound represented by structural formula (2), and the R6 and R7 groups in the second additive are cyclohexyl groups.

[0069] Example 5

[0070] In this embodiment, an electrolyte of the same system as that of embodiment 4 is prepared. The difference between this embodiment and embodiment 4 is that in the prepared electrolyte, the amount of the second additive is 0.3% of the mass percentage of the electrolyte.

[0071] Example 6

[0072] In this embodiment, an electrolyte of the same system as that of embodiment 4 is prepared. The difference between this embodiment and embodiment 4 is that in the prepared electrolyte, the amount of the second additive is 0.6% of the mass percentage of the electrolyte.

[0073] Example 7

[0074] The difference between this embodiment and embodiment 1 is that: in the prepared electrolyte, a first additive with a mass percentage of 0.5% and a second additive with a mass percentage of 0.3% are added, the first additive is a compound represented by structural formula (1), and the R1, R2, R3, R4 and R5 groups in the first additive are methyl groups; the second additive is a compound represented by structural formula (2), and the R6 and R7 groups in the second additive are cyclohexyl groups.

[0075] Comparative Example 1

[0076] Comparative Example 1 provides an electrolyte without adding the first additive and the second additive, the electrolyte comprising 2% by mass of lithium hexafluorophosphate (LiPF6) and 13% by mass of lithium bis(fluorosulfonyl)imide (LiFSI), and the remainder being an organic solute, wherein the organic solute comprises 30% ethylene carbonate (EC), 50% ethyl methyl carbonate (EMC) and 20% diethyl carbonate (DEC).

[0077] The electrolyte preparation method comprises: uniformly mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20 to obtain an organic solvent; and uniformly adding 2wt% of lithium hexafluorophosphate and 13wt% of lithium bis(fluorosulfonyl)imide into the organic solvent to obtain an electrolyte.

[0078] Table 1: Component ratios of the electrolytes prepared in Examples 1 to 7 and Comparative Example 1

[0079]

[0080] The electrolytes prepared in Examples 1 to 7 and Comparative Example 1 were used in lithium ion batteries to verify the efficacy of the present invention. The preparation process of the lithium ion battery is as follows:

[0081] (1) Positive electrode sheet: The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent acetylene black, and binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2, mixed and homogenized, coated on aluminum foil, and dried, cold pressed, and cut to obtain a positive electrode sheet.

[0082] (2) Negative electrode sheet: The negative electrode active material silicon dioxide, the conductive agent acetylene black, and the binder sodium carbon methyl cellulose are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:2:2, and then coated on a copper foil, dried, cold pressed, and cut to obtain a negative electrode sheet.

[0083] (3) Diaphragm: A polyethylene with a thickness of 9 μm was used as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm was coated on the base film to obtain a diaphragm.

[0084] (4) Battery assembly: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator being placed between the positive and negative electrode sheets to play an isolating role, and the bare battery cells are stacked; the bare battery cells are placed in an aluminum-plastic film, and then baked at 80°C to remove water, and then the corresponding electrolyte is injected and sealed. After that, the finished soft-package lithium-ion secondary battery is obtained through processes such as standing, hot and cold pressing, formation, clamping, and capacity division.

[0085] The performance of lithium-ion batteries assembled with the electrolytes of Examples 1 to 7 and Comparative Example 1 was tested. The test results are shown in Table 2. The test method is as follows:

[0086] At 25°C, charge the lithium-ion battery to 4.35V at 1 / 3C constant current, then charge at constant voltage to a current of 0.05C. Then discharge the battery to 2.5V at 1 / 3C constant current. Record the capacity C0, repeat the above charge and discharge steps 1000 times, and record the discharge capacity C1 of 1000 cycles. The capacity retention rate of the battery is C1 / C0×100%.

[0087] Table 2: Battery performance of lithium ion batteries prepared in Examples 1 to 7 and Comparative Example 1

[0088]

[0089] By comparing the test results of Examples 1 to 3 and Comparative Example 1, it can be seen that the addition of the first additive to the electrolyte can significantly improve the cycle performance of the lithium-ion battery. The first additive can be attached and fixed to the surface of the silicon-based negative electrode material through the Si-O-Si bond formed by polymerization, and the R1, R2, R3, R4 and R5 groups with large steric hindrance around the Si-O-Si bond are used to protect the surface of the silicon-based negative electrode material, eliminate the surface cracks caused by the volume expansion of the silicon-based negative electrode material during charging and discharging, thereby effectively inhibiting the negative impact of the volume expansion of the silicon-based negative electrode material during charging and discharging, and increasing the cycle capacity retention rate of the lithium-ion battery from 73.1% before adding the first additive to more than 79.8% after adding the first additive.

[0090] Furthermore, it can be seen from the test results of Examples 1 to 3 that within an appropriate dosage range (0.1% to 1% by mass of the electrolyte), as the amount of the first additive increases, the improvement in the cycle capacity retention rate of the lithium-ion battery also gradually increases, for example, from 79.8% when 0.1% of the first additive is added to 84.4% when 1% of the first additive is added.

[0091] By comparing the test results of Examples 4 to 6 with Comparative Example 1, it can be seen that adding only the second additive to the electrolyte has a certain improvement effect on the cycle performance of the lithium-ion battery, but overall, the improvement effect of adding the second additive alone on the cycle performance of the lithium-ion battery is not obvious, and the cycle capacity retention rate of the lithium-ion battery is only increased from 73.1% before adding the second additive to about 75% after adding the second additive. It can be seen that the addition of the second additive to the lithium-ion battery cycle capacity retention rate is only about 1% to 3%.

[0092] Moreover, it can be seen from the test results of Examples 4 to 6 that within the appropriate dosage range (0.1% to 0.6% of the mass percentage of the electrolyte), as the dosage of the second additive increases from 0.1wt%, the lithium-ion battery cycle capacity retention rate gradually increases; until the dosage of the second additive reaches 0.3wt%, the lithium-ion battery cycle capacity retention rate reaches the highest; and then when the dosage of the second additive continues to increase, the lithium-ion battery cycle capacity retention rate will decrease. It can be seen that when the second additive accounts for 0.3% of the mass percentage of the electrolyte, the improvement effect on the lithium-ion battery cycle performance is the best.

[0093] By comparing the test results of Example 2 and Example 7, it can be seen that the addition of the second additive on the basis of the first additive can further improve the cycle performance of the lithium-ion battery. Since the second additive can absorb water and acidic substances in the electrolyte, it can protect the first additive attached to the surface of the silicon-based negative electrode material, thereby helping to improve the inhibitory effect of the first additive on the volume expansion of the silicon-based negative electrode material, and further improve the cycle performance of the lithium-ion battery, for example, the cycle capacity retention rate of the lithium-ion battery is increased from 83.2% when only 0.5% of the first additive is added to 89.4% when 0.5% of the first additive and 0.3% of the second additive are added.

[0094] The present invention adds a first additive having a -Si-O-Si- group structure into an electrolyte, and uses the -Si-O-Si- group in the first additive to react with the residual silanol group on the surface of a silicon-based negative electrode material to form a Si-O-Si bond, so that the first additive is attached and fixed on the surface of the silicon-based negative electrode material, and when the volume of the silicon-based negative electrode material expands, the first additive diffuses on the surface of the silicon-based negative electrode material through the groups with large steric hindrance on the periphery of the Si-O-Si bond, thereby reducing the fresh exposed surface caused by the volume expansion of the silicon-based negative electrode material, and inhibiting the negative impact of the volume expansion of the silicon-based negative electrode material on the lithium-ion battery.

[0095] At the same time, the second additive added to the electrolyte in combination with the first additive can effectively absorb water and acidic substances formed in the electrolyte, protect the first additive attached to the surface of the silicon-based negative electrode material, and prevent the attached first additive from being ineffective due to acid hydrolysis, thereby helping to enhance the inhibitory effect of the first additive on the volume expansion of the silicon-based negative electrode material and further improve the cycle performance of the lithium-ion battery.

[0096] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An electrolyte, characterized in that: include: A lithium salt, an organic solvent and a first additive, wherein the first additive comprises one or more compounds represented by structural formula (1): Wherein, R1, R2, R3, R4 and R5 are each independently selected from methyl, tert-butyl, 1,1-dimethoxyethyl ether or 1,1-diethylpropyl.

2. The electrolyte according to claim 1, characterized in that: The compound represented by the structural formula (1) contains an unsaturated bond.

3. The electrolyte according to claim 1, characterized in that: The mass percentage of the first additive in the electrolyte is 0.1% to 1%.

4. The electrolyte according to any one of claims 1 to 3, characterized in that: The electrolyte further comprises a second additive, wherein the second additive comprises one or more compounds represented by structural formula (2): R6-B=C=N-R7 (2) Wherein, R6 and R7 are each independently selected from an alkane group or a cycloalkane group.

5. The electrolyte according to claim 4, characterized in that: The mass percentage of the second additive in the electrolyte is 0.1% to 0.6%.

6. The electrolyte according to claim 1, characterized in that: The organic solvent includes cyclic carbonate and linear carbonate.

7. The electrolyte according to claim 6, characterized in that: The cyclic carbonate includes one or both of ethylene carbonate (EC) and propylene carbonate (PC); the linear carbonate includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC).

8. The electrolyte according to claim 6, characterized in that: The mass percentage of the cyclic carbonate in the organic solvent is 10% to 40%; the mass percentage of the linear carbonate in the organic solvent is 10% to 80%.

9. The electrolyte according to claim 1, characterized in that: The lithium salt comprises lithium bis(fluorosulfonyl)imide and / or lithium hexafluorophosphate, and the lithium salt accounts for 8% to 20% by mass in the electrolyte.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrolyte for non-aqueous electrolyte battery, and non-aqueous electrolyte battery using same

    CN104380518A

  • Synthesizing method of vinylsilane

    CN109320543A

  • High-performance electrolyte and lithium ion battery containing same

    CN115360427A

  • Electrolyte solution, electrochemical device, and electronic device

    CN115528300A

  • Application of methyl trifluoroethyl carbonate, electrolyte, method for inhibiting manganese dissolution and battery

    CN115911570A

Cited By

  • Electrolyte and lithium ion battery

    CN119542542A

  • Electrolyte and lithium ion battery

    CN119542542B